Participatory design of a robot for demonstrating an epileptic seizure. (18th April 2019) - Zubrycki, Igor; Szafarczyk, Izabela; Granosik, Grzegorz
ABSTRACT: We present the methodology and results of participatory design of a robot for presenting an epileptic seizure and a scenario of the educational workshop using this robot. Children with epilepsy encounter stigma and stereotypes and may receive inadequate aid when having an epileptic seizure. The goal of the larger project was to use the prototype device in a series of workshops for improving teachers' actions during an epileptic seizure and their attitudes towards epileptic students. In this paper, we show how various design goals for an educational robot were accomplished to fit the needs of all identified stakeholders, particularly people with epilepsy. We used a co-design (participatory design) approach through a series of meetings participated by members of the association Polish Association for People Suffering from Epilepsy, students and faculty members of the biomedical engineering and robotics departments, teachers, psychologists and medical specialists (epileptologist, neurologist). These meetings created an opportunity for a better understanding of the (functional and nonfunctional) requirements and resulting tradeoffs and led the participants to find appropriate solutions. Participation of people with epilepsy in the design process allowed them to deal with the potentially stereotyped representation of themselves. The prototype robot, therefore, combined goals of various stakeholders, such as an accurate presentation of an epileptic seizure, lightweight, ease of use and control, while preserving the dignity of people with epilepsy. As a result of the co-designing process, an inexpensive robot was created and used in a series of 10 pilot workshops with 217 participants, mainly teachers of primary and middle schools. Teachers improved their understanding of epilepsy and suggested further improvements to the system. GRAPHICAL ABSTRACT: